2004
DOI: 10.1111/j.1474-9728.2004.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

The G/C915 polymorphism of transforming growth factor β1 is associated with human longevity: a study in Italian centenarians

Abstract: SummarySequence variations in a variety of pro-or anti-inflammatory cytokine genes have been found to influence successful aging and longevity. Because of the role played by the transforming growth factor β β β β 1 (TGF-β β β β 1) cytokine in inflammation and regulation of immune responses, the variability of the TGF-β β β β 1 gene may affect longevity by playing a role in inflamm-aging. Two polymorphisms, G/ A − − − − 800 and C/T − − − − 509 , located in the 5′ ′ ′ ′ region, and two missense polymorphisms, T/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 51 publications
1
65
0
6
Order By: Relevance
“…Recently, polymorphisms in a TGF-β binding protein (LTBP) and a TGF-β coreceptor (betaglycan) were found to associate with distinct COPD-related subphenotypes (31,36). Although a connection between TGF-β polymorphisms and serum levels was initially presumed based on a few publications, subsequent studies in larger and more heterogeneous populations have not consistently shown this association (37)(38)(39)(40). Immunohistochemical studies of COPD lung specimens show evidence of enhanced TGF-β signaling predominantly in the airway compartment (41)(42)(43).…”
Section: Figurementioning
confidence: 98%
“…Recently, polymorphisms in a TGF-β binding protein (LTBP) and a TGF-β coreceptor (betaglycan) were found to associate with distinct COPD-related subphenotypes (31,36). Although a connection between TGF-β polymorphisms and serum levels was initially presumed based on a few publications, subsequent studies in larger and more heterogeneous populations have not consistently shown this association (37)(38)(39)(40). Immunohistochemical studies of COPD lung specimens show evidence of enhanced TGF-β signaling predominantly in the airway compartment (41)(42)(43).…”
Section: Figurementioning
confidence: 98%
“…55,56 In fact, metformin treatment extends life span in the nematode Caenorhabditis elegans and in rodents. [57][58][59][60] We now propose that metformin, by weakening the ability of TGFb signaling to fully induce mesenchymal cell states in a variety of pathological processes including fibrosis, sclerosis and malignant progression (and likely by reducing TGFb-regulated inflammation and immune responsesinflamm-aging), [61][62][63] may provide an attractive therapeutic means to interfere with various age-related chronic diseases, thus molecularly behaving as a bona fide anti-aging modality. .…”
Section: Corollary: Rethinking Metformin As An Anti-aging Drug By Trementioning
confidence: 99%
“…Another cytokine gene often suggested is the transforming growth factor beta 1 gene (TGFβ1), which is involved, among others, in regulation of cellular proliferation and differentiation. In TGFβ1, the +915 polymorphism (rs1800471) and a haplotype including rs1800471 have been reported to be of relevance for longevity (Carrieri et al 2004).…”
Section: Introductionmentioning
confidence: 99%